THE EFFECT OF PERCEPTION ON LEARNING MEDIA AND VOCABULARY MASTERY ON ENGLISH SPEAKING ABILITY - Salamah Salamah; Muhammad Sulhan (Universitas Indraprasta PGRI, 2022)
This research aims to determine the effects of perception of learning media and vocabulary mastery on the English-speaking ability of eighth grade State Junior High School students in South Jakarta. The research method uses a survey method, with the random sampling technique with a sample of 60 students as research respondents. The results of the research are 1) There is a significant effect between the variables perception of learning media and vocabulary mastery together on the English speaking ability, this is evidenced by the results of Sig. 0.000 < 0.05 and Fo = 69.411. 2) There is a significant influence on the perception of learning media on English speaking ability with the results of Sig. 0.030 < 0.05 and Fo = 2222. 3) There is a significant effect of vocabulary mastery on English speaking ability with the results of Sig. 0.000 < 0.05 and Fo = 5.472.